Treatment of Scaphoid Waist Nonunion Using Olecranon Bone Graft and Stryker Asnis Micro Cannulated Screw: A Retrospective Study—80 Case Studies and 6 Years of Follow-Up - Poggetti, Andrea; Rosati, Marco; Castellini, Iacopo; Evangelisti, Gisberto; Battistini, Pietro; Parchi, Paolo; Lisanti, Michele (Journal of Wrist Surgery, 2015)
Background Screw fixation and bone grafting are the gold standard for scaphoid waist nonunion without avascular necrosis.Question/Purpose Assesses the scaphoid waist nonunion healing rate with use of an uncommon cancellous bone graft (olecranon) and an unusual fixation system (Asnis Micro Cannulated Screw System; Stryker Inc., Kalamazoo, MI, USA).Material and Methods A series of 102 consecutive patients were treated for scaphoid waist nonunion (without deformity). Of these, 80 patients subjected to clinical (Modified Mayo Wrist Score (MMWS), Jamar hydraulic dynamometer) and radiographic examination before and after surgery were evaluated. Ipsilateral olecranon cancellous bone graft and the ASNIS Micro 3.0-mm diameter screw, were used. The average follow up was 6 years (min 3; max 10).Results Radiographic consolidation was achieved in 90% of patients; dorsal intercalated segment instability (DISI) deformities were corrected in 71.4% of cases. Ninety percent improved the range of motion of the wrist and grip strength. All patients showed a significant reduction of peak force in the operated hand. In 6.25% we observed clinical and radiographic screw head–trapezium impingement. Twenty-six patients developed a degenerative wrist sign. The MMWS yielded 68 optimal, 8 good, and 4 bad results.Conclusions To treat scaphoid waist nonunions without misalignment, low-profile headed screw and olecranon bone graft allowed a high consolidation rate with positive results to long-term follow-up. The Asnis Micro 3.0 mm diameter screw may be a suitable option for treating scaphoid waist nonunion.Level of Evidence IV.
Keywords: scaphoid waist nonunion; olecranon bone graft; low-profile headed screws (Stryker Asnis Micro 3.0 mm diameter)